Fracture toughness of Ti-Si-N thin films. (April 2018) - Bartosik, M.; Hahn, R.; Zhang, Z.L.; Ivanov, I.; Arndt, M.; Polcik, P.; Mayrhofer, P.H.
Abstract: Ti-Si-N nanocomposite thin films usually consist of a few nm sized crystals embedded in an amorphous matrix. Here we study the influence of the Si content in Ti-Si-N films – prepared by reactive magnetron sputtering using Ti targets alloyed with intermetallic TiSi2 (to obtain Si contents of 0, 10, 15, 20, 25 at.% in the targets) – on fracture toughness ( K IC ) and hardness. Single cantilever bending experiments show that Ti-Si-N exhibits K IC values of up to 3.0 ± 0.2 MPa√m, which are significantly higher than those for TiN with 1.9 ± 0.2 MPa√m. Complementary nanoindentation experiments reveal also a higher hardness for Ti-Si-N with 34 ± 1 GPa as compared to 26 ± 1 GPa for TiN. The film structure is carefully studied by X-ray diffraction, X-ray photoelectron spectroscopy, and high-resolution transmission electron microscopy. Highlights: K IC of Ti-Si-N thin films is determined by single-cantilever bending tests. K IC and hardness depend on the Si content and the film structure. The film structure was studied by XRD, XPS, SEM, and HRTEM.